The Relationship Between Transformational Leadership, Training, And Employee Involvement As An Intervention Variable On Employee Performance - David Oloan (The Management Journal of Binaniaga, 2021)
This research is useful for examining the effects and relationships of the three variables, namely transformational leadership, training, and employee engagement on employee performance. The sample taken for this research amounted to 175 respondents who were selected randomly. The analytical method used in this research is Lisrel's Structural Equation Modeling (SEM) analysis. The results of the research show that transformational leadership does not directly affect employee performance, good training affects employee performance directly, and good employee involvement does not directly affect employee performance. According to the research results, the researcher gives advice to companies to be able to improve employee performance and ensure and comply with regulations in accordance with applicable law in an agency. The uniqueness of this research is that the researcher takes the variable regarding Employee Engagement in the construction industry (Real Estate) which has not been studied by many previous researchers.